USE OF ACTIVE ELEMENTS FOR PROVIDING SUITABLE VOLTAGE PROFILES AND PREVENT OVERLOADS IN RADIAL DISTRIBUTION NETWORKSRKS - Marko Vodenik; Matej Pintarič; Gorazd Štumberger (Journal of Energy Technology, 2023)
The article deals with the issue of providing suitable voltage profiles and preventing congestion of network elements in distribution networks. Active network elements and network users’ energy flexibility services are used to provide a suitable voltage profile and prevent congestion in distribution networks. The discussed active network elements include a transformer with on-load tap changer, reactive power compensation devices, energy storage systems, distributed energy resources, and network users’ energy flexibility services, where the active consumers adjust their consumption, production and storage of energy. Based on the Backward Forward Sweep load flow computation method, the case studies are performed for the discussed low voltage distribution network, where the measurement results were available. The case studies for preventing overload of the distribution transformer are performed using a battery energy storage system and network users’ energy flexibility services. The case studies for providing suitable voltage profiles are performed using all listed active elements and a combination of different active elements. In addition, to provide suitable voltage profiles, the existing conductors are replaced with conductors of a larger cross-section. Technically acceptable solutions that can provide a suitable voltage profile and prevent the overloading of network elements in the most demanding operating conditions are presented in this article.